Violence and birth outcomes: Evidence from homicides in Brazil - Martin Foureaux Koppensteiner; Marco Manacorda (Queen Mary University of London, School of Economics and Finance, 2015)
This paper uses microdata from Brazilian natality and mortality vital statistics between 2000 and 2010 to estimate the impact of in-utero exposure to local violence - measured by homicide rates - on birth outcomes. The estimates show that exposure to violence during the first trimester of pregnancy leads to a small but precisely estimated increase in the risk of low birthweight and prematurity. Effects are found in both rural areas, where homicides are rare, and in urban areas, where violence is endemic and are particularly pronounced among children of poorly educated mothers, implying that violence compounds the disadvantage that these children already suffer as a result of their households' lower socioeconomic status. Our estimates imply that homicides are responsible for around 10 percent of the incidence of low birthweight (<=2.5 kg) in urban areas of Brazil.
Keywords: I12; I15; I39; J13; K42; 330; Birth outcomes; Birthweight; Homicides; Stress; Brazil